2022
DOI: 10.3390/ijms23020670
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate Kinase 2 (PPK2) Enzymes: Structure, Function, and Roles in Bacterial Physiology and Virulence

Abstract: Inorganic polyphosphate (polyP) has been implicated in an astonishing array of biological functions, ranging from phosphorus storage to molecular chaperone activity to bacterial virulence. In bacteria, polyP is synthesized by polyphosphate kinase (PPK) enzymes, which are broadly subdivided into two families: PPK1 and PPK2. While both enzyme families are capable of catalyzing polyP synthesis, PPK1s preferentially synthesize polyP from nucleoside triphosphates, and PPK2s preferentially consume polyP to phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…PPK, EC 2.7.4.1, is primarily classified into two major families, PPK1 and PPK2. The PPK1 family can catalyze a reversible reaction using ATP and polyP n as substrates to generate ADP and polyP n+1 . , Although both enzyme families, PPK1 and PPK2, can synthesize polyphosphate (polyP), PPK1 primarily uses ATP to synthesize polyP, whereas PPK2 prefers to utilize AMP or ADP . PPK2 can use polyP as a donor to achieve GTP phosphorylation from GDP .…”
Section: Atp Regeneration System For Biocatalysismentioning
confidence: 99%
“…PPK, EC 2.7.4.1, is primarily classified into two major families, PPK1 and PPK2. The PPK1 family can catalyze a reversible reaction using ATP and polyP n as substrates to generate ADP and polyP n+1 . , Although both enzyme families, PPK1 and PPK2, can synthesize polyphosphate (polyP), PPK1 primarily uses ATP to synthesize polyP, whereas PPK2 prefers to utilize AMP or ADP . PPK2 can use polyP as a donor to achieve GTP phosphorylation from GDP .…”
Section: Atp Regeneration System For Biocatalysismentioning
confidence: 99%
“…The first phosphorylation is catalyzed by adenosine kinase (ADK), which consumes one ATP and releases one ADP. The subsequent two phosphorylation steps are catalyzed by the class II and I of the family 2 polyphosphate kinase (PPK2-II and PPK2-I), respectively, with the consumption of inorganic polyphosphate (polyP) . PPK2-I also regenerates ATP from ADP that is released from the first phosphorylation.…”
Section: Cofactor Sam Atp and Nad(p)h Regeneration And Connectionsmentioning
confidence: 99%
“…Literature mining indicated that those electron-dense structures could be polyP granules. To cope with an array of different stresses, including nutritional and oxidative stress, P. aeruginosa produces long polyP chains from both GTP and ATP [58,59]. PolyP are then packed into granules to serve as energy and phosphate storage [58,60].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…One stress response in P. aeruginosa is the formation of polyP granules that were observed in several strains upon incubation in plasma. PolyP are involved in many virulence phenotypes including motility and biofilm formation [59], and ppk mutants in Neisseria species were found previously to be strikingly more sensitive to killing by serum [72,73].…”
Section: Plos Pathogensmentioning
confidence: 99%